Ring-opening fluorination of cyclopropylmethanols and cycloprpanecarbardehydes with diethylaminosulfur trifluoride. (2nd February 2021) - Kirihara, Masayuki; Kikkawa, You; Nakamura, Riho; Nakakura, Kana; Suzuki, Yasuhiro; Muramatsu, Yukari
Graphical abstract: Highlights: Arylated cyclopropylmethanols react with DAST to produce homoallylic fluorides. Arylated cyclopropanecarbaldehydes reacts with DAST to produce 1, 4-difluorobut-1-enes. The reaction proceeds via a carbocation intermediate. Abstract: The reaction of cyclopropylmethanols bearing aromatic substituents on their cyclopropane rings with diethylaminosulfur trifluoride (DAST) effectively caused ring-opening fluorination to produce homoallylic fluorides. This reaction proceeded via a carbocation intermediate. DAST reacted with cyclopropanecarbaldehydes having electron donating aromatic substituents to cause ring-opening fluorinations with the addition of two fluorine atoms to afford 1, 4-difluorobut-1-enes.